Isolation and cloning of ABCA3 gene from Rasbora sarawakensis - Mohammad Azllan Shah, Mohd Isa (Universiti Malaysia Sarawak (UNIMAS), 2015)
In prokaryote, ATP-binding cassette facilitates the import of essential nutrients and the extrusion of toxins. They also participate in DNA repair and translation or regulation of gene expression. In eukaryotes, ABC proteins play role as efflux pumps. Based on previous study, mutation in ABCA3 gene are associated to cataract-microcornea syndrome and surfactant metabolism dysfunction. The model organism for this study is Rasbora sarawakensis that endemic at the island of Borneo. The objectives of this study are cloning and identification of ABCA3 gene from Rasbora sarawakensis and identify the expression of ABCA3 gene in Rasbora sarawakensis. Firstly, The ABCA3 gene isolated and cloned into pGEM-T easy vector. The vector inserted into XL-1 competent cell which produced 1.08 × 106 transformant/μg. The colony PCR conducted to confirm the presence of insert. Further confirmation was done by NotI restriction enzyme. The plasmid sent for sequencing and BLAST was conducted which shows 90% identity Danio rerio transporter 1, ATP-binding cassette, sub-family B (MDR/TAP) (tap1). Based on this study, the future expression identification and functional analysis of the gene in multixenobiotic mechanism can be carried out. Thus, establishing Rasbora sarawakensis as exotoxicological model for studying water condition in Sarawak.